Unifying Theories of Psychedelic Drug Effects - Swanson, Link R. (Frontiers in Pharmacology, 2018)
How do psychedelic drugs produce their characteristic range of acute effects in perception, emotion, cognition, and sense of self? How do these effects relate to the clinical efficacy of psychedelic-assisted therapies? Efforts to understand psychedelic phenomena date back more than a century in Western science. In this article I review scientific theories of psychedelic drug effects and highlight key theoretical features which have endured over the last 125 years of psychedelic science. First, I describe the subjective phenomenology of acute psychedelic effects using the best available empirical data. Next, I review late 19th-century and early 20th-century theories—model psychoses theory, filtration theory, and psychoanalytic theory—and highlight their shared theoretical features. I then briefly review recent neuropharmacological and neurophysiological findings. Finally, I describe some recent theories of psychedelic drug effects that leverage 21st-century cognitive neuroscience frameworks—entropic brain theory, integrated information theory, and predictive processing—highlighting their shared theoretical features and pointing out how they link back to earlier theories. From this analysis a key theoretical concept is identified which cuts across many theories past and present: psychedelic drugs perturb specific brain processes which normally sustain constraints on perceptual, affective, cognitive, and self-related neural systems. While a truly unifying theory has yet to emerge, I suggest that the enduring theoretical features and formalized frameworks highlighted in this article could form a groundwork for future unifying theories of psychedelic drug effects.